Conversational AI-Based Technological Solution for Intelligent Customer Service - Chumpitaz Terry, Alessandro (2024)
Virtual assistants are used to complement user navigation and experience through e-commerce platforms and online services. Several studies show that customer experience is significantly improved when virtual assistants exhibit human-like attention and provide personalized recommendations tailored to individual preferences and needs. To achieve this, the assistant can make use of Natural Language Processing, which enables understanding of human language along with responses. This study develops a virtual assistant focused on conversational AI which is implemented in a poultry retail’s website to improve customer experience. To validate the benefits of the implementation, we collected feedback from a group of 58 customers in the city of Lima that interacted with the virtual assistant. In this way, results showed that the virtual assistant generated a positive impact on customer service with an average of 83.66% across dimensions such as usability, functionality, and customer satisfaction.